PELATIHAN LITERASI DIGITAL DAN PEMANFAATAN AI (KECERDASAN BUATAN) UNTUK MENINGKATKAN KUALITAS KARYA TULIS ILMIAH SISWA SMA NEGERI 01 BOMBANA - Miranda; Nurdin; Nuralda; Armayanti; Ariel; Yuswandi; Haris. N. I (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Community Service (PKM) activity was motivated by the low digital literacy and scientific writing skills of students at SMA Negeri 01 Bombana, as well as the suboptimal use of artificial intelligence (AI) technology in the learning process. The activity aimed to improve students' understanding and skills in utilizing AI tools for literature searches, reference management, and the preparation of quality scientific papers. The training was conducted over two days using a participatory learning method involving 35 grade XI students through the stages of preparation, implementation (interactive lectures, demonstrations, guided practice, and group discussions), as well as evaluation and monitoring. The results of the activity showed a significant increase in participant understanding, with an average pre-test score of 68.5% increasing to 88.2% in the post-test (a 19.7% increase). In addition, 88.6% of participants successfully compiled an initial draft of the paper with the correct structure and using at least three valid academic references. Participants also demonstrated a good understanding of the ethics of using AI in academic writing. This activity is expected to contribute to strengthening the digital literacy ecosystem at SMA Negeri 01 Bombana and become a model for other schools in integrating AI into scientific writing learning